Susceptibility of PON1/PON2 Genetic Variations to Ischemic Stroke Risk in a Chinese Han Population - Pan Y; He B; Sun H; Xu T; Pan B; Wang S; Mei Y (Dove Medical Press, 2020)
Yuqin Pan,1,* Bangshun He,1,* Huiling Sun,1 Tao Xu,1 Bei Pan,1 Shukui Wang,1 Yanping Mei2 1General Clinical Research Center, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu Province, 210006, People’s Republic of China; 2Department of Laboratory Medicine, Nanjing First Hospital, Nanjing Medical University, Nanjing 210006, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shukui WangGeneral Clinical Research Center, Nanjing First Hospital, Nanjing Medical University, 68 Changle Road, Nanjing, Jiangsu 210006, People’s Republic of ChinaEmail shukwang@163.comYanping MeiDepartment of Laboratory Medicine, Nanjing First Hospital, Nanjing Medical University, 68 Changle Road, Nanjing, Jiangsu 210006, People’s Republic of ChinaEmail 4940556@qq.comBackground: Paraoxonases (PONs) are a family of orphan enzymes with multiple functions, including anti-inflammatory, antioxidative, antiatherogenic activities. Studies have suggested that genetic variations in PON1 and PON2 are associated with ischemic stroke (IS) risk; however, the conclusion remains unclear in the Chinese population.Methods: To investigate the susceptibility of genetic variations in PON1 and PON2 to risk of IS and its subtypes, this case–control study was carried out on a Chinese population comprising 300 IS patients and 300 healthy controls. Genotypes of six genetic variations in PON1 and PON2 were identified with an improved multiplex ligase detection–reaction technique.Results: PON1 rs662 was associated with increased risk of IS (CT vs. TT — ORadjusted 1.79, 95% CI 1.08– 2.97; p=0.025). Stratified analysis for patients by sex revealed that the significant association of PON1 rs662 with IS risk was maintained in the male cohort (CT vs. TT — ORadjusted 2.59, 95% CI 1.29– 5.21 [p=0.009]; CT/CC vs. TT — ORadjusted 2.03, 95% CI 1.05– 3.93 [p=0.036]), but not in the female cohort. Analysis according to IS subtype revealed that PON1 rs662 genetic variation was an increased risk in the subcohort of patients with large-artery atherosclerosis (CT/CC vs. TT — ORadjusted 2.31, 95% CI 1.09– 4.91; p=0.029), but not in patients with other types of IS.Conclusion: This study suggested that PON1 rs662 presented a potential risk of IS, especially for males, and this association was more obvious for large-artery atherosclerosis.Keywords: ischemic stroke, genetic variation, PON1, PON2